Multiple Rare Risk Coding Variants in Postsynaptic Density-Related Genes Associated With Schizophrenia Susceptibility - Hu, Tsung-Ming; Wang, Ying-Chieh; Wu, Chia-Liang; Hsu, Shih-Hsin; Tsai, Hsin-Yao; Cheng, Min-Chih (Frontiers in Genetics, 2020)
Objective Schizophrenia is a chronic debilitating neurobiological disorder of aberrant synaptic connectivity and synaptogenesis. Postsynaptic density (PSD)-related proteins in N-methyl-D-aspartate receptor-postsynaptic signaling complexes are crucial to regulating the synaptic transmission and functions of various synaptic receptors. This study examined the role of PSD-related genes in susceptibility to schizophrenia Methods We resequenced 18 genes encoding the disks large-associated protein (DLGAP), Homer, neuroligin (NLGN), neurexin, and SH3 and multiple ankyrin repeat domains (SHANK) protein families in patients with schizophrenia using semiconductor sequencing and analyzed the protein function of the identified rare schizophrenia-associated mutants via immunoblotting and immunocytochemistry. Results We identified 50 missense heterozygous mutations in 98 unrelated patients with schizophrenia, and in silico analysis revealed some as damaging or pathological to the protein function. Ten missense mutations were absent from the dbSNP database, the Exome Aggregation Consortium dataset, and 1,517 healthy controls from Taiwan BioBank. Immunoblotting revealed 8 missense mutants with altered protein expressions in cultured cells compared with the wild-type. Conclusion Our findings suggest that PSD-related genes, especially the NLGN, SHANK, DLGAP families, harbor rare functional mutations that might alter protein expression in some patients with schizophrenia, supporting rare coding variants that could contribute to the genetic architecture of schizophrenia.